Przyrodnicze, ekologiczne i techniczne aspekty rekultywacji terenów zdewastowanych przez kopalnictwo węgla brunatnego na obszarze trójkąta Łużyckiego = The natural, ecological and technical aspect of recultivation of the terrain's devastated by brown coal mining industry in east Germany - Haber, Zbigniew; Urbański, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the publicalion the devastation of landscape by brown coal mining industry in east Germany is described. This problem pertains also to country in similar range. After the world conference in Rio de Janeiro in 1992. - called ''peak of the world", the government of Germany (after the connection of both states) began to abolish the mines of brown coal andall the grounds after the mines are planned to design as regions for recreation purposes, naturally after filling up the excavations first with sand and then with water and planting young forests in surrounding of the lakes.
Keywords: kopalnie; rekultywacja gruntów pokopalnianych; Niemiecka Republika Demokratyczna